Transient Myopia and Hypotonia after Blunt Eye Trauma - Müge Çoban Karataf; Aysel Pelit; Yonca Ayd›n Akova (Türk Oftalmoloji Dergisi, 2011)
A patient whot received blunt trauma to the right eye one week ago referred to our clinic with complaints of low vision. Traumatic mMyopia and hypotonia were detected in the same eye after full ophthalmologic examination. The complaints of the patient completely disappeared after two weeks of medical treatment. Transient myopia and hypotonia after blunt ocular trauma may be temporary. After full ophthalmologic examination, proper treatment should be applied. (Turk J Ophthalmol 2011; 41: 191-3)